Design of Blast-Loaded Glazing Windows and Facades: A Review of Essential Requirements towards Standardization. (7th August 2016) - Larcher, Martin; Arrigoni, Michel; Bedon, Chiara; van Doormaal, J. C. A. M.; Haberacker, Christof; Hüsken, Götz; Millon, Oliver; Saarenheimo, Arja; Solomos, George; Thamie, Laurent; Valsamos, Georgios; Williams, Andy; et al.
Abstract : The determination of the blast protection level of laminated glass windows and facades is of crucial importance, and it is normally done by using experimental investigations. In recent years numerical methods have become much more powerful also with respect to this kind of application. This paper attempts to give a first idea of a possible standardization concerning such numerical simulations. Attention is drawn to the representation of the blast loading and to the proper description of the behaviour of the material of the mentioned products, to the geometrical meshing, and to the modelling of the connections of the glass components to the main structure. The need to validate the numerical models against reliable experimental data, some of which are indicated, is underlined.